Comparative study onneuroprotection of aqueous and ethanolicextracts of Calocybe indica (Purkayastha & Chandra) in neuro-2A-blastoma cell / Muhammad Taha Bennett - Muhammad Taha , Bennett (2021)
Mushrooms have gained worldwide popularity for both their nutritional and medicinal properties. Despite thousands of edible mushrooms worldwide, only a handful of mushrooms are available on a commercial scale or have been extensively studied for their therapeutic properties. A lot of research on health properties of mushrooms focus on chronic diseases such as cancer, heart disease and diabetes. In particular, a lot of research is currently focusing on neurodegenerative diseases such as Alzheimer’s disease. The current research focuses on Calocybe indica Purkayastha & Chandra (milky white mushroom), a relatively unknown mushroom. Fresh fruiting bodies of mushrooms were sliced then either freeze-dried or oven-dried before extracted using aqueous and ethanolic (99.8%) solvents. Cultures of mouse Neuro-2a-blastoma (N2a) cells were seeded into a 96-well plate and assessed by using a colorimetric 3-[4,5-dimethythiazol-2-yl]-2,5-diphenyltetrazolium bromide (MTT) assay with varying concentrations of the mushroom extracts (0-500 μg/mL) in order to determine potential neuroprotective properties of the mushroom. A negative control of N2a cells was used to determine cell viability and a positive control of H2O2 was used to determine cell toxicity. Oven-dried aqueous extract of Calocybe indica showed the highest cell viability (121%), followed by oven-dried ethanol extract (113%), freeze-dried aqueous extract (112%), and freeze-dried ethanol extract (105%). Neuroprotection against H2O2 followed a similar trend. Lower concentrations of Calocbye indica correlated with higher cell viability and neuroprotection. The total phenolic content and antioxidant activity of the mushroom were evaluated using a Folin-Ciocalteu reagent and 2,2-diphenyl-1- picrylhydrazyl (DPPH) dye.Oven-dried ethanol extracts showed the highest neuroprotective effects, the second highest total phenolic content (5.04 mg GAE/50 g dried mushroom weight), and the third highest antioxidant activity (12.89 mg/mL). Freeze-dried ethanol extracts showed the highest total phenolic content (7.2 mg GAE/50 g dried mushroom weight) and the highest antioxidant activity (EC50=8.63 mg/mL) despite having the lowest neuroprotective effects. A moderate positive correlation (R2 = 0.61) was found between total phenolic content and antioxidant activity. While phenolic content plays a considerable role in antioxidant activity, there is reasonable evidence that non-phenolic compounds contribute greatly to antioxidant activity and neuroprotection.